-5r-18r-(-16r)=14

Simple and best practice solution for -5r-18r-(-16r)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5r-18r-(-16r)=14 equation:


Simplifying
-5r + -18r + -1(-16r) = 14

Remove parenthesis around (-16r)
-5r + -18r + -1 * -16r = 14

Multiply -1 * -16
-5r + -18r + 16r = 14

Combine like terms: -5r + -18r = -23r
-23r + 16r = 14

Combine like terms: -23r + 16r = -7r
-7r = 14

Solving
-7r = 14

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Divide each side by '-7'.
r = -2

Simplifying
r = -2

See similar equations:

| secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 | | 0.66x+1=0.50 | | ln(5x+1)=ln(x+11) | | 9x=-11.7 | | 65x-6x=21x+23 |

Equations solver categories